Legal Analysis of the Role of the Aceh Government in Optimizing Health Provision in Aceh - Amzar Ardiyansyah; Nazaruddin Nazaruddin; Al Muttaqien; Usman Boini; T Yasman Saputra (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: Law Number 11 of 2006 concerning the Governance of Aceh mandates the responsibility of providing healthcare facilities to the Aceh Government. This study aims to determine the effectiveness of the Aceh Government’s healthcare infrastructure provision based on this legal framework. Research Methodology: Normative legal research using a regulatory and conceptual approach. Secondary data, consisting of primary, secondary, and tertiary legal materials, were qualitatively analyzed through document studies, literature, scientific journals, and related regulations. Results: The Aceh Government’s provision of health services is regulated by Article 183 of the Aceh Government Law in conjunction with Article 66 and Article 22 of the Qanun on Health, which constitutes asymmetric decentralization under Article 18A paragraph (1) of the 1945 Constitution. Health supervision is necessary through programs agreed upon by the executive and legislative branches of the government. Conclusions: The Aceh Government has attempted to maximize its authority through cross-sectoral collaboration to improve service quality. However, strengthening legal instruments, establishing stricter service standards, and revising Aceh Qanun Number 4 of 2010 concerning health are needed to ensure optimal service delivery. Limitations: Time constraints and difficulty in meeting respondents and informants in person. Contributions: This study provides a novel approach to legal reconstruction for special-autonomy-based health governance. The results contribute to strategic recommendations for the Aceh Government in reforming health sector policies. A limitation of this research lies in the focus of the analysis, which relies on normative data owing to the limited accessibility of direct field data.